Three year outcomes in infants with a family history of autism and/or attention deficit hyperactivity disorder - Tony Charman; Greg Pasco; Alexandra Hendry; Tessel Bazelmans; Nisha Narvekar; Amy Goodwin; Hanna Halkola; Mary Agyapong; Rebecca Holman; Jannath Begum Ali; Mutluhan Ersoy; Mark H. Johnson; et al. (Wiley, 2023)
Abstract Background Most research on early outcomes in infants with a family history (FH) of autism has focussed on categorically defined autism, although some have language and developmental delays. Less is known about outcomes in infants with a FH of attention deficit hyperactivity disorder (ADHD). Methods Infants with and without a FH of autism and/or ADHD, due to a first‐degree relative with either or both conditions, were recruited at 5 or 10 months. Three year outcomes were characterised using latent profile analysis (LPA) across measures of cognitive ability, adaptive functioning and autism, ADHD and anxiety traits (n = 131). We additionally ran an LPA using only autism and ADHD measures, and the broader LPA in an independent cohort (n = 139) and in both cohorts combined (n = 270). Results A Low Developmental Level + High Behavioural Concerns class had elevated autism, ADHD and anxiety scores, low cognitive and adaptive function, and included all but one child with autism. A Low Developmental Level + Typical Behaviour class had average cognitive ability and typical behaviour but low adaptive function. A Typical Developmental Level + Some Behavioural Concerns class had average cognitive and adaptive function but slightly elevated behaviour scores. A High Developmental Level + Typical Behaviour class had above average cognitive ability and typical behaviour. All four LPAs identified classes characterised by combinations of either, or both, Low Development Level and elevated behaviour scores, as well as a typically developing class. No classes had elevated autism or ADHD traits in isolation. Conclusions Some infants with a FH of autism or ADHD have atypical developmental and behavioural outcomes, but do not show strong autism or ADHD traits in isolation. The field needs to recalibrate aims and methods to embrace the broader transdiagnostic pattern of outcomes seen in these infants.